Caracterização de contaminantes ambientais emergentes e indicadores de potabilidade da água de consumo humano - Schneider, Silvana Isabel (2022)
The water quality for human consumption can be influenced by human activities through the forms of land uses and occupation. The general objective of this study was to characterize water for human consumption from rural properties located in municipalities in the State of Rio Grande do Sul and Santa Catarina (Brazil), regarding the presence of emerging environmental contaminants and other physical, chemical and microbiological variables that indicate water quality, as well as carrying out macroscopic environmental analyzes in shallow wells in the Uruguay River basin. The water samples were collected through two sampling campaigns (season 1 and 2), distributed in different land uses and occupations: dairy productivity, seasonal crops and swine production, and the shallow wells and their surroundings were visually evaluated, in rural properties. The values of the physical, chemical and microbiological analyzes were compared with the national and international legislations levels for water for human consumption. As results obtained for the macroscopic environmental analysis, it was verified that the shallow wells presented different classifications of degree of preservation, ranging from Excellent to Bad Class. Regarding the pH, apparent color, total hardness, fluorine, total ammonia, nitrite, nitrate and manganese variables, they were in accordance with the maximum permitted values (MPV) by current legislation. However, the turbidity, total iron, total coliforms and Escherichia coli variables presented values in disagreement with the standards established in the legislation. Total alkalinity, electrical conductivity, total solids, dissolved oxygen, biochemical oxygen demand, temperature, total phosphorus, total nitrogen and total nitrogen kjeldahl are not contemplated by the legislation, not having MPV for such variables. The different land uses and occupation did not interfere in the water physical and chemical variables. Thus, the macroscopic environmental analysis showed that the parameters that showed low preservation may be interfering with the water quality consumed by rural properties. The microbiological variables were quantified in the different lands uses and occupation, as well as in the different seasons studied, leading to the conclusion that the location of the shallow wells for human consumption, constructive aspects and their hygienic and sanitary conditions directly influenced the results obtained for these variables. Emerging environmental contaminants were detected in seasons 1 and 2 in all land uses and occupation, with pharmaceuticals and pesticides presenting concentrations lower than the MPV for drinking water for human consumption. It is believed that the presence of such compounds in the different land uses and occupation is due to the fact that the rural properties had other secondary activities, in addition to those studied, which may have influenced the results obtained.